Lipoatrophy associated with daily growth hormone injections. (8th September 2021) - Chhiba, Priya Darshani; Segal, David
Abstract : Summary: Recombinant human growth hormone therapy (rhGH) has been available since 1985 for a variety of conditions and has expanded the indications for rhGH therapy and the number of patients receiving therapy. The very nature of the therapy exposes individuals to years of injections. There are a number of well-known adverse events, however, a lesser-known and rarely reported adverse event of rhGH therapy is localized lipoatrophy. We report nine cases of localized lipoatrophy during rhGH therapy accounting for 14.5% of patients taking rhGH presenting to a single centre for routine follow-up over just a 2-month period. The development of localized lipoatrophy does not appear to be age, indication or dose-related but rather related to repeated administration of rhGH into a limited number of sites. The most likely putative mechanism is the local lipolytic action of growth hormone (GH) itself, although the possibility of an excipient-based interaction cannot be excluded. Given the high prevalence of this adverse event and the potential to prevent it with adequate site rotation, we can recommend that patients be informed of the possible development of localized lipoatrophy. Doctors and nurses should closely examine injection sites at each visit, and site rotation should be emphasized during injection technique education. Learning points: There are a number of well-known adverse events, however, a lesser-known and rarely reported adverse event of rhGH therapy is localized lipoatrophy. Examination of the injection sites at each visit by the treating healthcare practitioner. To advise the parents/caregivers/patients to change their injection site with each injection. To advise the parents/caregivers/patients to change the needles after every use. For parents, caregivers and patients to self-inspect their injection sites and have a high alert for the development of lipoatrophy and to then immediately report it to their doctor.